West African Economic and Monetary Union : Financial Sector Assessment Program-Technical Note on Systemic Risks and Macroprudential Policy Framework. (IMF Staff Country Reports; Country Report, 2022)
Since the 2008 Financial Sector Assessment Program (FSAP), the financial sector of the West African Economic and Monetary Union (WAEMU) has undergone major changes that have altered its risk profile. Three structural changes have played a key role since the 2008 FSAP: (i) the financial sector has grown significantly; (ii) regional banking groups have become dominant; and (iii) the high concentration of bank portfolios in sovereign exposures, which accounted for an average of 31 percent of banking assets at end-2020, are almost triple the level observed in 2004. These changes have altered the structure of systemic risks and vulnerabilities and raised the need for implementing reforms to strengthen the effectiveness of the macroprudential policy and banking supervision frameworks.